2022
DOI: 10.1108/eemcs-01-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ordeal or opportunity: IDPS journey through COVID-19 pandemic

Abstract: Learning outcomes This case enables students to understand the nature of a typical crisis and manage a crisis drawing insights from the protagonist handling of the crisis and from the various crisis management models in the literature. The rich description of the impact of COVID-19 pandemic on the world in this case enables students to understand the nature of a typical external crisis. The critical appraisal of the protagonist’s plans and actions to overcome the crisis enables students to appreciate the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The decreasing graph line from 2022 has been observed that can be attributed to several reasons as follows: (1) the number of citations of research articles that have been published in very recent years may not be correctly represented in just a couple of years. In most cases, a more realistic picture of the total number of citations may become visible after a few years have passed since the publication; (2) coronavirus disease 2019 (COVID-19) crisis has severely affected educational institutions, industries and other sectors from all over the world (Dimple et al ., 2022). However, an increasing trend line of average per year citations depicts the growing momentum of the research studies in the domain of GSCM and SSCM under a fuzzy environment.…”
Section: Results and Insightsmentioning
confidence: 99%
“…The decreasing graph line from 2022 has been observed that can be attributed to several reasons as follows: (1) the number of citations of research articles that have been published in very recent years may not be correctly represented in just a couple of years. In most cases, a more realistic picture of the total number of citations may become visible after a few years have passed since the publication; (2) coronavirus disease 2019 (COVID-19) crisis has severely affected educational institutions, industries and other sectors from all over the world (Dimple et al ., 2022). However, an increasing trend line of average per year citations depicts the growing momentum of the research studies in the domain of GSCM and SSCM under a fuzzy environment.…”
Section: Results and Insightsmentioning
confidence: 99%